Mobilisation Rates And Barriers To Mobilisation For Patients Who Receive Mechanical Ventilation In Australian Intensive Care Units - Harrold, M.; Webb, S.; Allison, Garry (2013)
Rationale: A proportion of patients admitted to the Intensive Care Unit (ICU) experience significant weakness that can affect function for up to two years. It has been hypothesised that early mobilisation may minimise weakness and restore function but conclusive evidences is not yet available for Australian patient populations. Furthermore, there is no baseline measure of mobilisation for Australian patients in intensive care. Methods: Aim: to quantify, terms of patterns, dosage and intensity of mobilisation and identify barriers of mobilisation in Australian ICUs. Design: an eight-week (four-week recruitment phase with a four-week washout phase), prospective, bedside audit. Patient Population: mechanically ventilated adults in Australian ICUs whose total length of stay was captured during the audit period. Data collection tool: a standardised, double sided form was used to collect information on mobilisation activities, frequence and duration; adverse events associated with mobilisation and barriers to mobilisation. Results: In total. 665 patients in 10 ICUs (eight tertiary, one country and one private) were audited. The percent of patients mobilised varied between sites from28.6% to 92.2% and averaged at 68.8%. Of the 1905 mobilisation activities recorded, 58.1% were weight bearing (standing, ambulating or utilisation of a tilt table) activities. The most common barriers to mobilisation were sedation in 29.2% of all patients, followed by the presence if an endotracheal tube (18.0%) and cardiovascular instability (14.7%). 46% of barriers could be partially or completely overcome. Conclusion: Mobilisation rates and patterns vary significantly across Australia. There are many barriers to mobilisation, some of which could be partially or completely overcome.